EFFECT OF THE ANTIOBESITY AGENT GARCINIA CAMBOGIA EXTRACT ON SERUM LIPOPROTEIN (a), APOLIPOPROTEINS A1 AND B, AND TOTAL CHOLESTEROL LEVELS IN FEMALE RATS FED ATHEROGENIC DIET - A. Altiner; A. Ates; F. Esen Gursel; T. Bilal (Journal of Animal and Plant Sciences, 2012)
The aim of the study was to investigate the effect of the antiobesity agent Garcinia cambogia extract, on serum lipoprotein (a), apolipoproteins A1 (apo A1) and B (apo B), and total cholesterol levels in atherogenic diet fed  rats. Thirty female, one year old Sprague-Dawley rats were separated to three equal groups. Group 1 (control group) was fed basal diet (2% liquid vegetable oil, 0% cholesterol). The diets of Groups 2 and 3 contained vegetable oil (2% liquid and 5% hydrogenated) and cholesterol (3%) in high levels. 4.5% (w/w) Garcinia cambogia extract was added to the diet of Group 3 after Day 45 up until the end of trial period. Blood samples were withdrawn on Days 0, 45 and 75. Serum lipoprotein (a), apo B, apo A1 and total cholesterol levels were determined by colorimetric methods. Serum lipoprotein (a) and apolipoprotein B levels were not significantly different between groups throughout the study. Serum apo A1 levels increased (P<0.05) towards the end of the study in Groups 2 and 3. Serum total cholesterol levels were significantly higher in Groups 2 and 3 than in the control group on Days 45 and 75. Garcinia cambogia extract did not have any significant effect on the analysed indices. The rising in serum apo A1 levels in Groups 2 and 3 was surprising, since apo A1 is a primary protein of high density lipoprotein and is protector from atherosclerosis. In conclusion, a %65 HCA containing diet was insufficient to lower atherosclerotic lipoprotein levels. Therefore, a higher dose of Garcinia cambogia extract should be experienced in future studies.
Keywords: Garcinia cambogia; Apolipoprotein; Lipoprotein ( a); Cholesterol; Rat.